Maternal Concerns Regarding Chewing Dysfunction in Children with Cerebral Palsy - Selen Serel Arslan; Numan Demir; Aynur Ayşe Karaduman (Galenos Yayinevi, 2022)
Aim:The aim of this study was to investigate the concerns of those mothers with children with cerebral palsy (CP) who were referred for a chewing evaluation, and the relationship between their chewing performance levels and the concerns of their mothers.Materials and Methods:A total of 55 children with CP, and their mothers were included in this study. Age, gender, height, weight, and type of CP were noted. The Karaduman Chewing Performance Scale (KCPS) was used to define the chewing performance level. Children with a KCPS level of 0 were categorized as "children without chewing dysfunction", and children with KCPS level 1 to IV were defined as "children with chewing dysfunction". The Turkish version of the Feeding/Swallowing Impact Survey (T-FS-IS) was used to evaluate the maternal concerns relating to the child's feeding and swallowing problems.Results:The mean age of children was 4.45±2.56 (minimum=2, maximum=11) years, of which 58.2% were male. There was a moderate to strong correlation between the KCPS and daily activities, worry, feeding difficulties and the total score from the T-FS-IS (p<0.001, r=0.71, r=0.64, r=0.72, r=0.74, respectively). The mothers of those children with chewing dysfunction reported more problems in the total score and all subscales of the T-FS-IS than those mothers of children without any chewing dysfunction (p<0.01).Conclusion:This study suggests that the chewing performance levels of children were associated with their mothers' concerns, and those mothers of children with CP who had chewing dysfunction have higher concerns relating to feeding-swallowing difficulties. This knowledge regarding maternal perception indicates that clinicians should consider the concerns of the mothers during the management of chewing dysfunction.